THE DETERMINANTS OF STOCK PRICE VOLATILITY IN PLANTATION INDUSTRY IN INDONESIA DURING 2016-2020 - Siawan, Resia Margareta; Lukman, Hendro (Graduate Program of Universitas Tarumanagara, 2023)
Stock prices in the market can react quickly to information from the market. This information makes stock prices volatile. The purpose of this study is to analyze the effect of dividend policy, leverage, growth in assets, and auditor quality on stock price volatility in the plantation industry listed on the Indonesia Stock Exchange for the period 2016 to 2020. This study uses multiple linear analysis using SPSS, and data collection by purposive sampling. The data used in this study is 75 data from 15 companies. The results of this study show that dividend and leverage policies affect stock volatility, while asset growth and auditor quality have no effect on stock volatility. The implication of this research is that companies that want to maintain the volatility of their shares must regulate leverage and dividend policies which are positive signals for investors in investment decisions.